Woman in Patriarchal Culture: Gender Discrimination and Intersectionality Portrayed in Bob Darling by Carolyn Cooke - Ida Rosida; Lestari Rejeki (Insaniyat : Journal of Islam and Humanities, 2017)
This  article  examines  gender  discrimination,  and  investigates  the  relation  between  gender  and social  class  relation  experienced  by  the  main  female  character,  Carla,  in  the  short  story  entitled Bob Darling by Carolyn Cooke. The method used in this study is descriptive qualitative applying the  concept  of  gender  discrimination  by  Mansour  Fakih  and  the  concept  of  intersectionality  by Kimberlé Crenshaw about the connection of multiple dimensions, such as gender and class in making discrimination. This study aims to find how the main female character that lives in the patriarchal culture is depicted in the story. Moreover, it is to show how social segregation strengthens the gender discrimination.  Gender  discrimination  is  unjust  treatments  and  assumptions  against  someone, particularly based on a person’s sex that leads to the role that he or she should play in the society. The  different  role  however,  leads  to  the  harm  and  the  loss  of  person’s  right  in  life  especially  for woman who lives in patriarchal culture. The results show that stereotype, subordination and violence against woman are experienced by the main female character in the society as the effect of gender discrimination. Then, social class as a division of individual classes based on levels of individual’s position in society that can be determined by wealth, education, occupation, and others has a part in gender discrimination. When the woman is on lower class, she has less power and authority so that  it  makes  a  stronger  discrimination  against  her.  In  conclusion,  in  the  patriarchal  culture,  the discrimination against woman is not only influenced by the gender itself, but also the social class.DOI: 10.15408/insaniyat.v1i2.4345